Aplicación web para el aprendizaje del idioma kichwa - Asimbaya Guanopatín, Blanca Lucero (2017)
The information about the Kichwa language is insufficient in the Language Cultural Center of the Technical University of Cotopaxi, according to current research, students and people who want to get knowledge about this language, mainly look for it in the Internet, they have noticed that there is poor information and there is no an application with respect to this topic. Therefore, the purpose of this study is to have a better knowledge about Kichwa acquired by students in the Language Cultural Center through the development and implantation of a web application that let students evaluate their own performance regarding the table of contents studied in the Module. Through the use of this application, the contents in which students have a low score can be understood through a detailed explanation. Practical activities will be in line with the adequate use of Grammar and speech recognition in order to improve the writing and pronunciation of words in Kichwa. SCRUM was used because it mainly focuses in the development of the required software in which data is important....